Impressment into the Imperial Armada in the Independece and Cisplatine Wars - Fonseca, Paloma Siqueira (2020)
Impressment was a practice used by the Brazil Navy to man the ships of the Imperial Armada in the wars of independence of Brazil (1823) and Cisplatin (1825-1828). The waves of recruits were deposited in presiganga, prison-ship Navy, in the port of Rio de Janeiro. At that time, the Navy took the boating experience of merchant seamen and employed men accused of vagrancy, giving them a useful target for the establishment of the Empire of Brazil.